Notas sobre el comportamiento de Cistus salviaefolius tras desbroces, laboreos, fertilizaciones y aplicación de fitocidas (Pastos, 1977)
The Cistus salviaefolius L. is an invading and competitive species in the pastures of Quercus súber covered mounts. In order to control it we carried out some triáis of (1) rotary cutting, (2) rotary cutting -+- ploughing and (3) rotary cutting + ploughing -+- fer- tilizing, under Q. súber trees that covered 40 % aind (4) rota'ry cutting in 25 % shade: The inventory of the number of plants shows according to the comparative plots which did not undertake any treatment at all, that the reinvasion is fast and very intense. In triáis with phytocides before emergence (atrazine, simazine, bromacil and diuron) the results of control of Cistus were not as good as the ones we got in the comparative plots that were just ploughed; and besides that they produced a lack of pasture for nearly two years. The phytocides did not damage the Q. súber when using those dosis. Those results have improved the knowledge of how meteorological factors could affect the germination abi'lity of Cistus salviaefolius, that could be useful for the coming studies directed to its control. 246